Learning environments research in English classrooms - Lim, C.; Fraser, Barry (Springer, 2018)
Although learning environments research has thrived for decades in many countries and school subjects, English classroom environment research is still in its infancy. This article paves the way for expanding research on English classroom environments by (1) reviewing the limited past research in English classrooms and (2) reporting the first study of English learning environments in Singaporean primary schools. For a sample of 441 grade 6 students, past research in other subjects was replicated in that a modified version of the What Is Happening In this Class? questionnaire was cross-validated, classroom environment was found to vary with the determinants of student sex and ethnicity, and associations emerged between students’ attitudes and the nature of the classroom environment.